Enhancing Farmers' Group Digital Financial Literacy Through Record-Keeping Application Training - Hilda Porawati; Ari Kurniawan; Tanto Tanto; Mazwan Mazwan; Ilham Saputra (Yayasan Keluarga Guru Mandiri, 2026)
Digital transformation offers farmer groups new ways to strengthen administrative governance, yet financial records are often kept manually and without standardized procedures. This community service program aimed to improve farmer groups' digital financial literacy through training on the Farmers' Budgeting System Application and to examine its initial effects on record-keeping orderliness, transparency, and the efficiency of cash recapitulation. Using a pre-experimental one-group pre-test–post-test design, we conducted a participatory, hands-on training session with 11 participants in a face-to-face setting at Politeknik Jambi. Data were collected via a pre/post knowledge test, an operational skills checklist, and a perception questionnaire. Participants' mean knowledge score increased from 46.55 (pre-test) to 82.45 (post-test), and most participants mastered core functions for entering income and expense transactions and generating summary reports for recapitulation. Early outcomes included faster administration, neater and better-documented records, and more transparent cash reporting. We conclude that application-based training can rapidly raise digital financial literacy and improve basic financial governance in farmer groups. This program contributes a practical, replicable training model and preliminary evidence supporting the use of digital record-keeping tools to strengthen community-based financial management.